(untitled) (Journal of Advanced Research in Social Sciences, 2020)
At the point when we discuss about atrocities against women, we don’t allude to some new happenings yet it is an old phenomenon that has been permitted to go on. All through the ages from one period to another period women have been left to the abominations and carelessness. In all social orders, societies, areas or religious communities’ women have been subject to confront brutality from higher to the lower level and to the present day in India this has come to an alarming extent. The situation of women in Indian culture has been held under continuous dormancy while the exploitation against them is increasing repeatedly. The explanation, most likely, is that woman is considered as more vulnerable sex when contrasted with their contrary sex. This paper explains how women are being exploited in our patriarchal societies. The present paper also discusses about why women are being neglected in our male dominated society. The paper will also focus on various incidences of rape cases that occur in India.